Comparative analysis of phenolic content in potato genotypes and propagation materials - Rita Asakaviciute; Jolanta Jurkeviciute; Nijole Ruziene; Ingrida Radveikiene; Erika Kubiliene (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science)
The objective of this study was to evaluate the agronomic characteristics and total phenolic content (TPC) of four Lithuanian potato (Solanum tuberosum L.) varieties – VB Venta, Goda, VB Meda, and VB Aista – across different propagation stages, including in vitro plantlets (m0), minitubers (m1), tubers (m2), and first-class (E1) seed potatoes. Morphological traits, yield, and starch content were recorded for each cultivar. Ethanolic extracts were prepared from potato samples at four developmental stages, and TPC was quantified spectrophotometrically. Statistical comparisons were made to assess differences among varieties and stages. TPC was highest in the in vitro plantlet stage (m0), particularly in VB Venta (182.4 ± 52.1 µg/g), and declined with developmental progression. VB Meda showed relatively stable TPC across all stages, while Goda and VB Aista had lower levels at maturity. These results suggest that phenolic compound accumulation in potato is strongly influenced by genotype and developmental stage. The varieties VB Venta and VB Meda demonstrate high antioxidant potential and are promising candidates for functional food applications. These findings support the integration of biochemical traits into potato breeding and propagation programmes to enhance nutritional quality.